Islamic Leadership Accountability Of Umar Bin Abdulaziz: A Lessons Towards A Good Governance In Nigeria - Ibrahim Musaddad, Aliyu; Mohammed Inuwa, Abubakar (IKONOMIKA, 2020)
There is no doubt leadership has been given a tremendous place and a key positioning in Islam, Qur’an, Sunnah and the consensus of Ulama’u (Muslim scholars) have made it apparent about the necessity of leadership among the Muslim community. Most recently, the issue of leadership in Nigeria has become a major concern to the Nigerians. Whilst some research has been conducted to examine the solutions to Nigerian leadership, little attention has been paid to Islamic approaches of accountability which is the vital pillar of governance as the key towards sustainable leadership in Nigeria. This study therefore seeks to explore the lessons from leadership and accountability during the caliphate of Umar bin Abdulaziz (R.A) as a panacea to Nigerian Leaders.The methodology of the study relies on critical and comprehensive analysis of the existing published literature related to the topic. Hence, data collection is effected through the qualitative method. The findings of this study revealed that there are lots of lessons and wisdoms that Nigerian government could acquire from the history of caliphate Umar such as his reformations and innovations in governing the state as reflected in siyasah shar’iyyah which can be solution for practicing good governance in Nigeria. Based on the findings, it was recommended that fear of Allah and believing in accountability is the best option for leaders.Key words: Leadership, Islam, Model, Accountability, Good Governance.